Effectiveness of Instruction Program on Osteoporosis Old Age Performance about Prevention of Fall - Ali Abdul Razzaq Naser; Khalida Mohammed Khuder (Migration Letters, 2023)
Objectives: The aim of this study is to assess the effectiveness of instruction program on osteoporosis old age performance about prevention of fall Methods: A quantitative approach using a quasi-experimental design was used in the present study with the application of a pre-tests/ post-tests approach for the study group and control group. Non-probability (purposive) sample of (100) osteoporotic patients were selected from senior homes. The study sample in this research was divided into two groups; (50) osteoporotic patients for the study, which were exposed to the health instructional program, and (50) osteoporotic patients for the control group. Results: This study reveals that the level of total performance among participants towards the prevention of falls reveals that most osteoporotic patients had a low performance level in preventing falls (96%) at pre-test results. The post-test results indicate that all osteoporotic patients in the study group had a high level of performance in preventing falls (100%), while the osteoporotic patients in the control group had a low level of performance in preventing falls for the pretest and post-test. According to the levels of balance and risk for falls among participants which reveals that most of osteoporotic patients had moderate risk of falls (88%) at pre-test results, whil the post-test results indicates that all osteoporotic patients in the study group were having low risk of fall (100%), while the most of osteoporotic patients in control group were holding moderate risk for falling (78%) at pretest and (94%) of them had moderate fall risk at posttest. The effectiveness of instructional program on fall prevention performance, the results refer to highly significant difference among osteoporotic patients’ performance in the study group at p-value= 0.00 respectively, and there is no significant difference among osteoporotic patients’ performance in the control group at p-value= 0.05 respectively, Also the effectiveness of instructional program on fall prevention performance, the results refer to highly significant difference among osteoporotic patients’ balance level between pretest and posttest in the study group at p-value= 0.00 respectively, and there is high significant difference among osteoporotic patients’ balance level between pretest and posttest in the control group at p-value= 0.05 respectively. Conclusion: The instructional program is effective in improving performance levels. This study suggests further research on a larger sample should be carried out to estimate the incidence of osteoporosis and osteoporotic fractures related to falls in Iraq and induce the practical application of the instructions, precautions, management methods, preventive measurements, and monitoring its impact on the long-term lifestyle of the seniors with osteoporosis.